Highways, Market Access, and Spatial Sorting - Stephan Fretz; Raphael Parchet; Frédéric Robert-Nicoud (Center for Economic Studies and ifo Institute (CESifo), 2017)
We design a spatial model featuring workers embodied with heterogeneous skills. In equilibrium, locations with improved market access become relatively more attractive to the high-skilled, high-income earners. We then empirically analyze the effects of the construction of the Swiss highway network between 1960 and 2010 on the distribution of income at the local level, as well as on employment and commuting by education level. We find that the advent of a new highway access within 10km led to a long-term 19%-increase of the share of high-income taxpayers and a 6%-decrease of the share of low-income taxpayers. Results are similar for employment data decomposed by education level, as well as for in- and out-commuters. Highways also contributed to job and residential urban sprawl.
Keywords: D31; O18; H54; R11; R23; 330; transportation; highway; market access; income sorting